Precarious livelihoods: Examining the intersection of fish work and ecological change in coastal Jamaica. Issue 1 (28th November 2019) - Marschke, Melissa; Campbell, Donovan; Armitage, Derek
Abstract: Precarity has not been applied in the context of fisheries‐based work, even as working conditions in fisheries are emerging to be a real issue. There has been limited analysis of fish work outside the media spotlight or how changing ecological and biophysical conditions (e.g. climate change and its effects) intersect with poor working conditions. We use insights from fieldwork along the southwest coast of Jamaica, to ask the following questions: (a) what does precarity mean for mixed‐gear fishers working in the nearshore context, particularly with reference to working conditions and (b) how do changing ecological and biophysical conditions intersect with working conditions to further influence fisher precarity? Our results highlight how fishing livelihoods in Jamaica are generally precarious because of limited options for fish workers in this sector. Even so, certain fishing activities are far riskier than others – particularly for compressor dive fishers – and that levels of precarity are differentiated by age and fishing gear ownership. A more integrative (or social and ecological) approach to precarity analysis helps characterize and give nuance to fish work operating across time and space, and shows how such work intersects with ecological decline and further drives precarity. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.